Stereospecific route to 5,11-methanomorphanthridine alkaloids via intramolecular 1,3-dipolar cycloaddition of nonstabilized azomethine ylide: Formal total synthesis of (+/-)-pancracine - Pandey, Ganesh; Banerjee, Prabal; Kumar, Ravindra; Puranik, Vedavati G. (Organic Letters, 2005)
[GRAPHICS] The core structure of the complex pentacyclic 5,11-methanomorphanthridine alkaloids is constructed stereospecifically in one step employing an intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The strategy is demonstrated by accomplishing the formal total synthesis of (+/-)-pancracine.

Synthesis and characterization of ferrocenylchalcogenopropargyl complexes [Fe(eta(5)-(C5H4ECH2C)-C-I CH)(2)] (E-I = Se, S) and their reactions to form unusual ferrocenyl-containing metal clusters with eclipsed Cp rings and new five-membered (FeECH)-C-I = - Mathur, P.; Singh, V. K.; Mobin, Shaikh M.; Srinivasu, C.; Trivedi, R.; Bhunia, A. K.; Puranik, Vedavati G. (Organometallics, 2005)
{The new bis(chalcogenopropargyl)ferrocene complexes [Fe(eta(5)-C(5)H(4)E(I)CH(2)CdropCH)(2)] (E-I = Se, 1; E-I = S, 2) have been prepared by treatment of the dilithiated [Fe(eta(5)-C5H4Li)(2)] with Se or S powder, followed by reaction with propargyl bromide. Reaction of 1 and 2 with [Fe2M(mu(3)-E)(2)(CO)(9)] (E = S, Se and M = Fe, Ru) forms new clusters which feature an unusual five-membered (FeECH)-C-I=CCH2 ring with a pi bond between the olefinic unit and the Fe atom, and the Cp rings adopt an eclipsed arrangement. The structures of 1 and [Fe(eta(5)-C5H4E(I)-CH(2)CdropCH) (eta(5)-C5H4{Fe2M(CO)(8)(mu-E)((ECHCCH2)-C-I)})] (M = Fe

Synthesis of cis bis-beta-lactams via Staudinger cycloaddition reaction using C-2-symmetric 1,2-diamines - Shaikh, A. L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2005)
An efficient stereoselective synthesis of bis-beta-lactams via cycloaddition reaction (Staudinger reaction) of ketenes with bisimines derived from C-2-symmetric 1, 2-diamines is described. The reaction provided diastereomeric mixture of meso and C-2-symmetric cis-bis-beta-lactams with higher selectivity for meso-bis-beta-lactams. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; Staudinger cyclo-addition reaction; stereoselective synthesis

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Supramolecular self-assembled ruthenium-polypyridyl framework encapsulating discrete water cluster - Deshpande, Megha S.; Kumbhar, A. S.; Puranik, Vedavati G.; Selvaraj, K. (Crystal Growth & Design, 2006)
Keywords: 4; 4 `-dimethoxydiphenylmethane; benzylsulfonic acid; Condensation of anisole; p-formaldehyde; Zr-TMS-BSA

Synthesis, characterization, X-ray structure and DNA photocleavage by cis-dichloro bis(diimine) Co(III) complexes - Ghosh, Smita; Barve, A. C.; Kumbhar, A. A.; Kumbhar, A. S.; Puranik, Vedavati G.; Datar, P. A.; Sonawane, U. B.; Joshi, Rohini R. (Journal of Inorganic Biochemistry, 2006)
Keywords: Acetic acid; acrylic acid; oxidative conversion of propane; rare earth-doped Mo-V-Sb catalysts

Synthetic studies toward macrocidins: an RCM approach for the construction of the central cyclic core - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The central macrocyclic core of the macrocidins was constructed using RCM as the key reaction. A preliminary investigation dealing with the key reactions, that is, the Dieckmann cyclization and the RCM, revealed that RCM of the beta-ketoamide is better than RCM of the corresponding acyltetramic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: acyltetramic acid; Lacey-Dieckmann cyclization; macrocidins; Ring closing metathesis

Stereoselective synthesis of spiro-beta-lactams using D-(+)-glucose derived chiral pool: remarkable influence of the torquoelectronic effect - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2007)
Diastereoselective synthesis of spiro-beta-lactams via [2+2] cycloaddition reaction of imines and chiral ketenes is described. The chiral ketene was prepared from commercially available, inexpensive D-glucose. Although, theoretically four diastereomers are possible, the reaction yielded only two diastereomers stereoselectively in good to moderate yields. The stereochemical outcome of the reaction was in accordance with the torquoelectronic model. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; spiro-beta-lactams; Staudinger reaction; stereoselective synthesis

Synthesis and glycosidase inhibitory studies of pentahydroxyindolizidines: D-Glucose-Derived aziridine-2-carboxylate approach - Kumar, K. S. Ajish; Chaudhari, Vinod D.; Puranik, Vedavati G.; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2007)
D-Glucose -derived aziridine-2-carboxylate I was converted into a-amino aldehyde 7, which, after Wittig olefination, asymmetric dihydroxylation, hydrogenation followed by LiAlH4 reduction, and N-Cbz protection, afforded two diastereomeric pyrrolidines 11a and 11b with sugar appendages. Removal of the 1,2-acetonide functionality in 11a/11b and reductive animation gave the pentahydroxyindolizidine alkaloids 6g and 6h, respectively, with (S) absolute configurations at the ring junctions. The glycosidase inhibitory activities of these compounds were studied.
Keywords: asymmetric dihydroxylation (AD); Iminosugars; indolizidine; N-methylmorpholine; N-oxide (NNIO)

Synthesis, NMR, X-ray crystallography and bioactivity of some alpha-aminophosphonates - Prasad, Gandavaram Syam; Krishna, Jadaprolu Radha; Manjunath, Manubolu; Reddy, Obulam Vijaya Sarathi; Krishnaiah, Musali; Reddy, Cirandur Suresh; Puranik, Vedavati G. (Arkivoc, 2007)
The synthesis of some new alpha-aminophosphonates (4a-l) was accomplished by one pot reaction of equimolar quantities of 2-amino-4-chlorophenol (1), various aromatic aldehydes (2a-l) and diethylphosphite (3) in dry toluene at reflux temperature. Products 4a-l were characterized by IR, H-1, C-13, P-31 NMR and in the case of 4g by X-ray crystal diffraction data.
Keywords: alpha-Aminophosphonates; Antibacterial

Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.

Synthesis, structure, and reactivity of diazoketiminato complexes of platinum(II) and palladium(II): cytotoxic properties of a platinum complex - Pratihar, Jahar Lal; Shee, Biswaranjan; Pattanayak, Poulami; Patra, Debprasad; Bhattacharyya, Arindam; Puranik, Vedavati G.; Hung, C. H.; Chattopadhyay, Surajit (European Journal of Inorganic Chemistry, 2007)
{Reaction of the 2-(arylazo)anilines Ar-N = N-C6H4NH2 [
Keywords: CFD; hydro processing; scale-down; scale-up; trickle bed

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Synthesis of 1,2,3-triazole and 1,2,3,4-tetrazole-fused glycosides and nucleosides by an intramolecular 1,3-dipolar cycloaddition reaction - Anegundi, Ramakrishna I.; Puranik, Vedavati G.; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2008)
Various 1,2,3-triazole and 1,2,3,4-tetrazole fused multi-cyclic compounds were synthesized from carbohydrate derived azido-alkyne and azido-cyanide substrates. The acid sensitive 1,2-O-isopropylidene group of the furanosyl sugar was utilized for diversification to glycosides and nucleosides under Fischer glycosidation and Vorbruggen's conditions, respectively.

Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol

Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

Synthesis, structure and reactivity of azosalophen complexes of palladium - Pattanayak, Poulami; Pratihar, Jahar Lal; Patra, Debprasad; Puranik, Vedavati G.; Chattopadhyay, Surajit (Polyhedron, 2008)
The ligands 2-(arylazo)-1-N-salicylidene phenylamine, H(2)L(sal), (where H represents the dissociable protons upon complexation) afford stable orthopalladated complexes, [(L(sal))Pd], upon treatment with Na(2)[PdCl(4)]. The dinegative anionic (L(sal))(2-) ligands bind Pd(II) in a tetradentate (C, N, N, O) fashion with a distorted square planar geometry. The newly synthesized palladium complexes underwent oxygen insertion into the Pd-C bond with mCPBA (m-chloroperbenzoic acid) or TBHP (terbutylhydroperoxide)/[VO(acac)(2)] leading to the formation of stable azosalophen complexes of Pd(II) with the (O, N, N, O) coordination mode of the oxygenated ligand. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-(arylazo)-1-N-salicylidene phenylamine; azosalophen complex; orthopalladation; oxygen insertion

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Stereoselective synthesis of (+)-isoindolo-beta-carboline - Wakchaure, Prasad B.; Puranik, Vedavati G.; N. P. Argade (Tetrahedron-Asymmetry, 2009)
Starting from homophthalic anhydride and (S)-tryptophan, the stereoselective synthesis of (+)-isoindolo-beta-carboline has been described via the corresponding homophthalimide, its chemoselective oxidative ring contraction, and the intramolecular dehydrative ring closure followed by a geometry-specific demethoxycarbonylation. (C) 2009 Elsevier Ltd. All rights reserved.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

Synthesis, electronic structure, DNA and protein binding, DNA cleavage, and anticancer activity of fluorophore-labeled copper(II) complexes - Bhat, Satish S.; Kumbhar, Anupa A.; Heptullah, Hussain; Khan, Ayesha A.; Gobre, Vivekanand V.; Gejji, Shridhar P.; Puranik, Vedavati G. (Inorganic Chemistry, 2011)
Two mononuclear fluorophore-labeled copper(II) complexes [Cu(nip)(acac)](+) (2) and [Cu(nip)(2)](2+) (3), where fluorophore is 2-(naphthalen-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (nip) (1) and acac is acetylacetone, have been synthesized aid characterized by various techniques. The ligand 1 and complex 2 are structurally characterized by single-crystal X-ray diffraction. The coordination geometries around the copper are square planar in solid as well as solution state as evidenced by electron paramagnetic resonance (EPR) spectroscopy. The density functional calculations carried out on 1-3 have shown that electron-rich regions in the highest occupied orbital are localized on the naphthalene end partly on the phenanthroline moiety. Both complexes 2 and 3 in dimethyl sulfoxide (DMSO) exhibit near square planar structure around the metal ion in their ground state. Time-dependent density functional theory (TD-DFT) calculations reveal that Cu(II) ion in complex 2 shows tetrahedral coordination around the metal while 3 retains its square planar geometry in the lowest excited state. The interaction of complexes with calf-thymus DNA (CT DNA) has been explored by using absorption, emission, thermal denaturation, and viscosity studies, and the intercalating mode of DNA binding has been proposed. The complexes cleave DNA oxidatively without any exogenous additives. The protein binding ability has been monitored by quenching of tryptophan emission in the presence of complexes using bovine serum albumin (BSA) as model protein. The compounds showed dynamic quenching behavior. Further, the anticancer activity of the complexes on MCF-7 (human breast cancer), HeLa (human cervical cancer), HL-60 (human promyelocytic leukemia), and MCF-12A (normal epithelial) cell lines has been studied. It has been observed that 3 exhibits higher cytotoxicity than 2, and the cells undergo apoptotic cell death.

Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines

Synthesis of tetrahydro-5-azaindoles and 5-azaindoles using pictet-spengler reaction-appreciable difference in products using different acid catalysts - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron, 2011)
Pictet-Spengler condensation of 2-(aryl)-2-(1H-pyrrol-2-yl)ethanamines using conventional acid catalysts like TMSCl or TFA resulted in the formation of substituted 5-azaindoles involving a tandem one pot four steps reaction sequence. By contrast use of glacial acetic acid furnished the targeted tetrahydro-5-azaindoles in diastereoselective manner. These were readily dehydrogenated to 5-azaindoles. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 2-(Aryl)-2-(1H-pyrrol-2-yl)ethanamines; 4; 7-Disubstituted-5-azaindoles; 7-Disubstituted-tetrahydro-5-azaindoles; Diastereoselective Pictet-Spengler reaction

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation

Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations - Kundu, Tanaya; Chowdhury, Abhishek Dutta; De, Dipanwita; Mobin, Shaikh M.; Puranik, Vedavati G.; Datta, Anindya; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
{An effective anion sensor, [Ru-II(bpy)(2)(H2L-)](+) (1(+)), based on a redox and photoactive {Ru-II(bpy)(2)} moiety and a new ligand (H3L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F-) and acetate (OAc-) ions. Crystal structures of the free ligand, H3L and [1](ClO4) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO4) shows that the benzimidazole N-H of H2L- is hydrogen bonded with the pendant carboxylate oxygen while the imidazole N-H remains free for possible hydrogen bonding interaction with the anions. The potential anion sensing features of 1(+) have been studied by different experimental and theoretical (DFT) investigations using a wide variety of anions, such as F-, Cl-, Br-, I-, HSO4-, H2PO4-, OAc- and SCN-. Cyclic voltammetry and differential pulse voltammetry established that 1(+) is an excellent electrochemical sensor for the selective recognition kof F- and OAc- anions. 1(+) is also found to be a selective colorimetric sensor for F- or OAc- anions where the MLCT band of the receptor at 498 nm is red shifted to 538 nm in the presence of one equivalent of F- or OAc- with a distinct change in colour from reddish-orange to pink. The binding constant between 1(+) and F- or OAc- has been determined to be logK = 7.61 or 7.88, respectively, based on spectrophotometric titration in CH3CN. The quenching of the emission band of 1(+) at 716 nm (lambda(ex) = 440 nm

Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Strong metal-metal coupling in mixed-valent intermediates [Cl(L)Ru(mu-tppz)Ru(L)Cl](+), L = beta-diketonato ligands, tppz=2,3,5,6-tetrakis(2-pyridyl)pyrazine - Kundu, Tanaya; Schweinfurth, David; Sarkar, Biprajit; Mondal, Tapan Kumar; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
Five diruthenium(II) complexes [Cl(L)Ru(mu-tppz)Ru(L)Cl](1-5) containing differently substituted beta-diketonato derivatives (1: L = 2,4-pentanedionato; 2: L = 3,5-heptanedionato; 3: L = 2,2,6,6-tetramethyl-3,5-heptanedionato; 4: L = 3-methyl-2,4-pentanedionato; 5: L = 3-ethyl-2,4-pentanedionato) as ancillary ligands (L) were synthesized and studied by spectroelectrochemistry (UV-Vis-NIR, electron paramagnetic resonance (EPR)). X-ray structural characterisation revealed anti (1, 2, 5) or syn (3) configuration as well as non-planarity of the bis-tridentate tppz bridge and strong d pi(Ru-II) -> pi*(pyrazine, tppz) back-bonding. The widely separated one-electron oxidation steps, (RuRuII)-Ru-II/(RuRuIII)-Ru-II and (RuRuIII)-Ru-II/(RuRuIII)-Ru-III, result in large comproportionation constants (K-c) of >= 10(10) for the mixed-valent intermediates. The syn-configurated 3(n) exhibits a particularly high K-c of 10(12) for n = 1+, accompanied by density functional theory (DFT)-calculated minimum Ru-N bond lengths for this (RuRuIII)-Ru-II intermediate. The electrogenerated mixed-valent states 1(+)-5(+) exhibit anisotropic EPR spectra at 110 K with average values < g > of 2.304-2.234 and g anisotropies Delta g = g(1)-g(3) of 0.82-0.99. Metal-to-metal charge transfer (MMCT) absorptions occur for 1(+)-5(+) in the NIR region at 1660 nm-1750 nm (epsilon approximate to 2700 dm(3) mol(-1) cm(-1), Delta nu(1/2) approximate to 1800 cm(-1)). DFT calculations of 1(+) and 3(+) yield comparable Mulliken spin densities of about 0.60 for the metal ions, corresponding to valence-delocalised situations (Ru-2.5)(2). Rather large spin densities of about -0.4 were calculated for the tppz bridges in 1(+) and 3(+). The calculated electronic interaction values (V-AB) for 1(+)-5(+) are about 3000 cm(-1), comparable to that for the Creutz-Taube ion at 3185 cm(-1). The DFT calculations predict that the (RuRuIII)-Ru-III forms in 12(+)-52(+) prefer a triplet (S = 1) ground state with Delta E (S = 0 - S = 1) similar to 5000 cm(-1). One-electron reduction takes place at the tppz bridge which results in species [Cl(L)Ru-II(mu-tppz(.-)) Ru-II(L)Cl](-) (1(.-)-3(.-), 5(.-)) which exhibit free radical-type EPR signals and NIR transitions typical of the tppz radical anion. The system 4(n) is distinguished by lability of the Ru-Cl bonds.

Supported copper triflate as an efficient catalytic system for the synthesis of highly functionalized 2-naphthol Mannich bases under solvent free condition - Dindulkar, Someshwar D.; Puranik, Vedavati G.; Jeong, Yeon Tae (Tetrahedron Letters, 2012)
Various heterogeneous catalysts (Lewis acid) have been prepared and screened for the synthesis of Betti bases in an attempt to reduce the environmental hazards associated with the conventional homogeneous Lewis acid system. And we found especially Cu(OTf)(2)center dot SiO2 catalyzes the three-component coupling of aldehyde, 2-naphthol, and alicyclic amine to generate Betti base with high efficiency under neat conditions without additional co-catalyst or additive in air. The reaction is not sensitive to water and occurs smoothly in water as well. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Betti bases; single-crystal XRD; Solvent-free; Supported copper triflate; Three-component coupling

Supramolecular synthon transferability and gelation by diprimary ammonium monocarboxylate salts - Das, Uttam Kumar; Puranik, Vedavati G.; Dastidar, Parthasarathi (Crystal Growth & Design, 2012)
Earlier studies revealed that primary ammonium dicarboxylate (PAD) salts possessed gelling ability, and many such salts displayed a 1D columnar hydrogen bonded network (observed in primary ammonium monocarboxylate (PAM) salts) on either side of the dicarboxylate end of the anion. In the present study, a new series of diprimary ammonium monocarboxyate (DPAM) salts have been prepared with the aim of achieving supramolecular synthon transferability (the same 1D columnar hydrogen PAM bonded network on either side of the diammonium cation) in these salts. Single crystal X-ray diffraction studies revealed that, in 47% of the DPAM salts, such supramolecular synthon transferability indeed took place. Some of the DPAM salts also showed gelation ability. The gels were characterized by DSC, rheology, electron microscopy, and atomic force microscopy. Structure property correlation using single crystal and powder X-ray diffraction data on a selected gel was also attempted.

Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one

Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Synthesis and X-ray single crystal structure of a cadmium(II) acetophenone thiosemicarbazone complex and its use as a single-source precursor for the preparation of CdS nanocrystallites and thin films - Palve, Anil M.; Joshi, Pranaya V.; Puranik, Vedavati G.; Garje, Shivram S. (Polyhedron, 2013)
{A cadmium(II) acetophenone thiosemicarbazone complex has been prepared and characterized by elemental analysis, infrared and nuclear magnetic resonance (H-1 and C-13H-1) spectroscopic techniques. Its single crystal structure has also been determined. The compound is found to be monoclinic, space group C2/c, with a = 12.1020(3) angstrom
Keywords: CdS; Nanocrystallites; Single source precursor; Thin films; Thiosemicarbazone complex

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Synthesis, characterization, and crystal structure determination of palladacycles of para-substituted 2-thiobenzylazobenzenes - Bhattacharjee, Tirtha; Kalita, Mukul; Chakravarty, Debamitra K.; Barman, Pranjit; Puranik, Vedavati G. (Journal of Coordination Chemistry, 2014)
Bichelated neutral palladacycles (1-3), [Pd(L)Cl], were synthesized from reaction of the new potential tridentate (C,N,S) ligands, 2-thiobenzylazobenzene (L-1), 4'-methyl-2-thiobenzylazobenzene (L-2), and 4'-chloro-2-thiobenzylazobenzene (L-3) with sodium tetrachloropalladate(II), Na-2[PdCl4], in ethanol. The compounds were characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible, and thermogravimetric analysis. The crystal structures of L-2 and 1-3 were determined by single-crystal X-ray diffraction. In 1-3, the geometry around palladium remains almost square planar, coordinated to carbon, nitrogen, and sulfur of the ligand forming a bichelated cyclopalladate complex. The C-H center dot center dot center dot Cl type intermolecular hydrogen bonds, weak pi center dot center dot center dot pi, C-H center dot center dot center dot pi, and van der Waals interactions are believed to be the stabilizing forces for the crystal packing of these palladacycles.
Keywords: 2-Thiobenzylazobenzene; CNS-donor ligand; crystal structure; Palladacycles; Thermogravimetric analysis

Synthesis, characterization and molecular structures of homologated analogs of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone - Salunke-Gawali, Sunita; Pawar, Omkar; Nikalje, Milind; Patil, Rishikesh; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath (Journal of Molecular Structure, 2014)
Four analogues of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone (where n-alkyl is methyl in L-1Br, ethyl in L-2Br, propyl in L-3Br and butyl in L-4Br) are synthesized and characterized. A reaction mechanism is proposed for the formation of L-1 Br to L-4Br from the starting material 2,3-dibromo-1,4-naphthoquinone. The v(N-H) frequency in the FT-IR spectra is affected by the intramolecular hydrogen bonding in L-1Br to L-4Br and is observed similar to 3267 cm(-1) in L-2Br. A shift of similar to 25 cm(-1) is observed in the v(C-Br) frequency in all the compounds as compared to 2,3-dibromo-1,4-naphthoquinone (627 cm(-1)). A broad charge transfer band is observed between 400 and 600 nm in the UV-Vis spectra, which imparts red colour to all the compounds. Molecular structures of L-2Br and L-3Br were studied by single crystal X-ray diffraction studies. Molecules of L-2Br crystallize in Pca2(1), whereas the molecule L-3Br crystallizes in the P-1 space group. Molecules of L-2Br forms a polymeric chain through N-H...O interaction and forms beautiful butterfly like arrangement of molecules when viewed down the `a' axis. Ladder like polymeric chain of molecules is observed in L-3Br via C-H...O and N-H...O interactions. Every alternating neighbouring chains of L-3Br, show pi-pi stacking interactions between the quinonoid rings of the molecules, however this interaction is not observed in L-2Br. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Dibromo-1; 4-naphthoquinone; Aminonaphthoquinone; hydrogen bonding; Michael addition; pi-pi stacking

Synthesis, spectroscopic characterization and structural investigations of new adduct compound of carbazole with picric acid: DNA binding and antimicrobial studies - Saravanabhavan, Munusamy; Sathya, Krishnan; Puranik, Vedavati G.; Sekar, Marimuthu (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
Carbazole picrate (CP), a new organic compound has been synthesized, characterized by various analytical and spectroscopic technique such as FT-IR, UV-Vis, H-1 and C-13 NMR spectroscopy. An orthorhombic geometry was proposed based on single crystal XRD study. The thermal stability of the crystal was studied by using thermo-gravimetric and differential thermal analyses and found that it was stable up to 170 degrees C. Further, the newly synthesized title compound was tested for its in vitro antibacterial and antifungal activity against various bacterial and fungal species. Also, the compound was tested for its binding activity with Calf thymus (CT) DNA and the results show a considerable interaction between CP and CT-DNA. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity and DNA-interaction; CP adduct; Single crystal XRD; TG-DTA

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.